Identification of National Road Maintenance Needs Based on Strategic Plan of Directorate General of Bina Marga (2015-2019) - Rizky Ardhiarini (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2016)
The enhancement of connectivity between the main corridors of the economy in South Sumatera, as a purpose of the Strategic Plan of Directorate General Bina Marga and also an objective of MP3EI, Master Plan for Acceleration and expansion of Indonesia's Economic Development which is an ambitious plan by the Indonesian government to accelerate the realization of becoming a developed country would be able to achieve on the requirement of good condition on performance and pavement. In order to support the optimal condition of the road, the identification of road management was conducted to determine the necessity of road maintenance based on technical conditions and importance level of development of the road traversed. The management program proposed is expected to be used as a baseline in determining the maintenance of the road network in South Sumatera from 2015 until 2019. This research used Multi-criteria Analysis (MCA) method, which consists of: (1) road network performance, covering width of roadways, traffic flow, V/C ratio, travel speed and travel time of the vehicle, and (2) pavement condition, with IRI, SDI, and the proportion of good pavement condition as a parameter. Multi-criteria analysis used combined road condition assessment score and importance level of development of the area traversed by. This analysis was conducted from 2015 until 2019. The research concluded that maintenance necessity in 2015 were dominated by routine maintenance (95.86% of the total length), then in 2016 until 2019 the needs were dominated by routine maintenance (near 100% of the total length). As the maintenance applied, a vast amount of total road length fulfilled as an achievement target. The results are follows: (a) 100% with width of roadways ≥ 7 meter, (b) 97.83% with V/C ratio < 0.75, (c) 18.50% with travel speed > 60km/hour, (d) 17.32% with travel time (TT) < 1.6 jam/100km, (e) 100% with good pavement condition > 95%, (f) 90.37% with IRI < 4 m/Km, and (g) 91.59 with SDI < 50. Yet with the achievement of 100% of total road length with a minimum width 7.0 meter, and 90.37% of total road length with an IRI less than 4.0 m/km in 2019, the impact was not significant on increasing length of the road with a travel time (TT) less than 1.6 jam/100km. The condition is caused by there are no maintenance requirements concerning the improvement of the substandard road geometric.